TINJAUAN KEBERLANJUTAN LINGKUNGAN Studi Kasus PDAM Kabupaten Bondowoso: TINJAUAN KEBERLANJUTAN LINGKUNGAN Studi Kasus PDAM Kabupaten Bondowoso - Gusti Dian Prayogi; Widiar Onny Kurniawan (Majalah Ekonomi, 2023)
This research aims to analyze the implementation of environmental accounting in PDAM Bondowoso, particularly concerning the management of production waste. In modern business, it is crucial for companies to consider financial aspects, social welfare, and the environment. Although the Republic of Indonesia Law number 23 of 1997 regarding Environmental Management identifies waste as operational residue requiring special handling, conventional accounting practices in PDAM Bondowoso tend to inadequately incorporate environmental aspects into their financial reports. This study aims to contribute to the development of environmental accounting practices, especially for similar companies, to reduce the negative impacts of production waste. The results are expected to serve as a basis for practical guidelines in applying environmental accounting, strengthening the understanding of the importance of environmental management in the context of a company's sustainability and its surroundings. Environmental pollution is the degradation of the environment caused by human activities or uncontrolled external factors. Environmental accounting is necessary to measure, assess, and disclose costs related to waste management. Allocating environmental costs requires systematization to ensure corporate accountability. The stages of environmental cost treatment include identification, recognition, and grouping of expenses associated with managing environmental impacts during the production process. This research provides a clearer perspective on the importance of incorporating environmental aspects into corporate accounting to implement sustainable practices, prevent negative impacts of production waste, and promote a balance between financial, social, and environmental considerations. Keywords: Environmental Accounting; Sustainability; Financial Reporting.